ETNOPEDAGOGI DALAM TRADISI TINJU ADAT NTT - Kota Bena, Agustinus Rikarda; Saputra, Ardi Wina (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This research aims to revitalise the educational value in the tradition of Tinju Adat Etu, in Flores, East Nusa Tenggara. The educational value is revitalised by interpreting the language represented in the rituals and symbols in the Indigenous Boxing tradition. This research method is qualitative with an ethnographic research approach. The data sources in this research are indigenous people, traditional leaders, and perpetrators of Tinju Adat in Wuliwalo Village, Flores NTT. Data were collected by means of interviews and observations. Data analysis was carried out using rite and symbol interpretation techniques in the Tinju Adat tradition. The results showed that there were educational values in 3 Traditional Boxing rites, precisely in the rites of (1) Ka'o Mata, (2) Tuka Etu, and (3) Bhela-bhelu. The results also show that there are 6 symbols of the Tinju Adat tradition that contain educational values. The six symbols are (1) Ragi, (2) Tiwuri, (3) Iket Talu, (4) Ca'I Leda, (5) Nggong and Wea, (6) Tameng.